Comparing two cases of the non-fluent and semantic variants of primary progressive aphasia using neuropsychological, narrative and acoustic measures - Karpathiou, Nomiki; Kambanaros, Maria (My University, 2019)
Introduction. PPA is a degenerative syndrome characterized by progressive, relatively isolated, loss of language function. The current consensus criteria for PPA identify three variants: the non-fluent/agrammatic variant of PPA (nfvPPA), the semantic variant of PPA (svPPA) and the logopenic variant of PPA (lvPPA) (Gorno-Tempini et al., 2011), each with a distinct profile of language impairment, distribution of atrophy and underlying pathology. The aim of this study is to compare the clinical presentation of the nfPPA and svPPA, in two Greek-speaking individuals with PPA, using a battery of neuropsychological tests, narrative analysis and acoustic measures. Greek is a highly inflected and stem-based language, underrepresented in the literature on PPA research. Participants. The first participant with the nfvPPA is a 61-year-old man with 6 years of formal education. The second participant with the semantic variant of PPA is a 73-year-old man with 9 years of education. Both participants were assessed five years post-onset. The first participant had a sum of boxes score of 9 on the FTLD-modified Clinical Dementia Rating, whereas the second one a score of 6. The control group consisted of 12 neurologically healthy adults, native Greek speakers, with a mean age of 68.08 (SD = 5.52) years and a mean of 13 (SD = 3.19) years of education. Procedure. Participants were evaluated using a comprehensive battery of neuropsychological tests. Quantitative production analysis (QPA) (Saffran, Berndt, & Schwartz, 1989) was used for the narrative analysis of a picture description and a story retell task. Acoustic analysis was performed in order to calculate temporal measures of participants’ speech. Statistical analysis. Performance of each subject was compared to that of the control sample using the Crawford and Howell’s method (Crawford, Garthwaite, & Porter, 2010). T values were also calculated to compare the scores of the two subjects with reference to the control sample (Crawford, Garthwaite, & Wood, 2010). Results. The participant with the nfvPPA performed worse than the participant with the svPPA on tasks of working memory (p = 0.025), syntactic comprehension (p = 0.014) and reading fluency for words (p < 0.001). Furthermore, he was slower in temporal measures of speech production (Table 1). The participant with the svPPA was more impaired in confrontation naming (p < 0.001), single word comprehension (p < 0.001) and object semantics (p = 0.001). The narrative production measures that differed significantly between the two participants were speech rate (slower for the nfvPPA participant, p = 0.007), average pause duration (longer for the nfvPPA participant, p < 0.001), false starts per min (more for the nfvPPA participant, p = 0.045), proportion of nouns (lower for the svPPA participant, p = 0.012) and closed class words (lower for the nfvPPA participant, p = 0.016). Discussion. The results confirm the distinctive features of both PPA variants: motor speech and syntactic processing difficulties in the case of the participant with the nfvPPA, anomia and a single word comprehension deficit in the case of the participant with the svPPA. Neuropsychological testing combined with narrative and acoustic analysis have enabled the documentation of speech and language deficits present in these cases of PPA and the comparison of the two participants.
Keywords: Primary progressive aphasia; Semantic variant; Non-fluent agrammatic variant; Narrative analysis; Greek; Acoustic measures; Neuropsychological assessment